Investigation of a landslide prone area, Bukit Tinggi, Malaysia using integrated geophysical engineering and environmental isotope techniques / Tariq (Moh’d Khier) Alkhamaiseh - Tariq (Moh’d Khier), Alkhamaiseh (2019)
Population growth and extension of settlements over risky areas have resulted in an increased impact of a natural disaster. Slope failures, landslides and subsidence of foundation have been identified as the most commonly occurring natural disasters after floods. On the other hand, a detailed analysis of the triggering factors is often hindered by the lack of information gathered from the field measurements. The vicinity of Sekolah Menengah Kebangsaan Bukit Tinggi in Pahang province is considered as one of the natural terrain areas (weathered granite) which are prone to landslide hazards and should be effectively monitored prior to any forewarning of slope movements. This study is conducted to improve understanding between the triggering factors of a landslide in the study area and the suitable preventive measures by using integrated geophysical, geotechnical, and environmental isotope techniques. The 2D inversion results of resistivity technique suggest the presence of a two-layer structure. Moreover, an apparent break in the unit is indicative of the presence of weak fractured zone. As also demonstrated clearly by the seismic refraction data, the depth to bedrock (a sharp boundary interface approximately at a depth of 15 m) varies, which is mainly attributed to variation in thickness of the overlying backfill material. Furthermore, the obtained results from Hydrogen and Oxygen isotopes present a regression line that represents the local meteoric water line as follows: δD = 7.416 δ18O + 7.428 (R2 = 0.88). This line is similar to the global meteoric water line and also to the recent global relationship of δD = (8.17 ± 0.07) δ18O + (11.27 ± 0.65). The isotope data of surface and groundwater used for this study are all distributed along the local meteoric water line, indicating that the stable isotopes of both surface and groundwater do not have effects of evaporation and can thus be regarded as conservative. From this study, a good relationship between the electrical (resistivity) and geotechnical (soil strength) properties with the empirical equation RS= 31.733 (N60) -165.88 and regression coefficient R2=0.77 is observed. Meanwhile, based on the correlation between the elastic property and weathering profile, the subsurface materials were divided into three zones as follows: Residual soil, highly weathered granite, and moderately weathered granite with p-wave velocity 300 – 900 ms-1, 900 – 1800 ms-1, 1800 – 3000 ms-1 respectively. Moreover, according to integrated results obtained from different techniques, the slip surface zone is located at a depth of 15 - 23 m from the ground surface where the materials show some large differences of properties based on the primary velocity obtained. The weak zone may occur due to water infiltration downward through surface cracks, which intensively weakened the subsurface materials mainly by chemical weathering. This study thus helped us to investigate and predict various physical properties of the subsurface material (soils and rocks) with reduced cost and to apply them in understanding the underground structural characteristics of the landslide prone study area.